(untitled) (International Journal of Architectural Engineering Technology, 2025)
In post-conflict settings, recovery is commonly measured by rebuilt infrastructure and restored governance, yet these metrics overlook subtler forms of resilience rooted in everyday life. This paper argues that the reopening of small shops and the revival of local markets constitute a distinct and measurable axis of recovery, one that restores economic function while reweaving social bonds, cultural memory, and communal dignity. Focusing on Syria, the study reframes commerce as a site of healing where souks and storefronts operate simultaneously as livelihoods, social spaces, and symbolic claims to normalcy and resistance. The paper’s novelty lies in linking Syria’s historical position on the Silk and Incense Routes with contemporary grassroots market restoration, producing a historically informed framework that treats market revival as both heritage practice and adaptive urban strategy. Methodologically, the research combines ethnographic observation, oral histories, and spatial mapping across detailed case studies—Zamalka and Mukhayyam Al-Yarmouk souks in Damascus and Al-Madinah souk in Aleppo—complemented by comparative analysis of Mostar and Beirut to identify transferable dynamics and divergent trajectories. Findings show that market reopening accelerates informal governance, stimulates micro-enterprise networks, and regenerates public sociability, producing resilience outcomes that conventional reconstruction metrics miss. The paper concludes by proposing policy recommendations for recovery planners and heritage practitioners: prioritize micro-retail capacity building, protect informal trading spaces, and integrate market-sensitive indicators into recovery assessments. The relaunch of commercial services, the study contends, does more than reactivate income streams; it reclaims daily life and reaffirms communal continuity in post-crisis settings.